Advocating Classics Education – a new national project. Issue 36 (5th December 2017) - Hall, Edith; Holmes-Henderson, Arlene
Abstract : The 'Advocating Classics Education' (ACE) project is an initiative led by Professor Edith Hall and Dr Arlene Holmes-Henderson, based at King's College London. The project seeks to extend the availability of Classical Civilisation and Ancient History (CC/AH) qualifications to learners in non-fee-paying schools across the United Kingdom. To do so, Professor Hall has been awarded a Leadership Fellowship of £250, 000 from the Arts and Humanities Research Council (AHRC). The project's full title is 'Studying Classical Civilisation in Britain: recording the past and fostering the future' and it runs from 1 st May 2017 to 31 st August 2018.